Analisis Butir Soal Pekan Ulangan Harian pada Materi Persamaan Kuadrat di SMPN 1 Astanajapura - Reza Oktiana Akbar; Edi Prio Baskoro; Agus Ibrahim (Journal on Education, 2025)
The aim of this research is to determine the content validity, construct validity, reliability, difficulty level, discriminating power, and the effectiveness of distractors of the weekly test questions for SMPN 1 Astanajapura. These questions were independently created by the teachers of SMPN 1 Astanajapura and have not been previously tested or analyzed. The population or subjects of this study are ninth-grade students, selected using purposive sampling, meaning not all ninth-grade students were used as samples, only 3 out of 8 classes were chosen as samples. Data collection in this research employed documentation and interview methods. The analysis results show good content validity and construct validity. The reliability value is 0.88 with a confidence level of 0.60. The distribution proportion of difficulty levels is easy and moderate, with 70% being easy and 30% moderate. As for the discriminating power of the questions, 70% were categorized as sufficient, and 30% as good. The effectiveness of the distractors needs improvement to be used effectively.